Soil and Fertilizer Management for Vegetable Production in Florida - G. D. Liu; E. H. Simonne; K. T. Morgan; G. J. Hochmuth (EDIS)
This document is HS711, one of a series of the Horticultural Sciences Department, UF/IFAS Extension.